First Language (L1) Use in the EFL Classroom: Perceptions of Students and Teachers - Noliza Hasrina; Zulfadli A. Aziz; Siti Sarah Fitriani (English Education Journal, 2018)
This study was aimed to find out the perceptions of teachers and of students about the use of their L1 (Bahasa Indonesia) in their EFL classroom in the teaching-learning processes. A quantitative method was used for this study which used a questionnaire as the instrument. This study was conducted at the MAN High School at Darussalam with 94 respondents, consisting of three teachers and ninety one students from grade two from the three different departments (XI IPS, XI IPA and XI IAG). The results from the questionnaires showed that the respondents predominantly used their L1 rather than the L2 in their English EFL Classes for teaching-learning activities such as when explaining materials which were hard to understand, giving instructions on materials and tasks to explaining new vocabulary and for helping students to feel more comfortable and more confident in learning English. In this regard, the use of their L1 in their English classes was aimed at having good communications between the teachers and their students and between students and students. In addition, the use of their L1 was very helpful for students to understand their English lessons and to improve the students' motivation in learning English EFL